Plastibell circumcision in neonates and infants at tertiary care centre - Shinde, Nandkishor D.; Moinuddin, Mohammad; Danish, A. N. M. Owais (International Surgery Journal, 2018)
Background: Circumcision is the most common surgical procedure in children worldwide. The aim of this study was to study the safety and complication of Plastibell circumcision in neonates and infants. Methods: This prospective study of 420 male children less than 1 years who underwent Plastibell circumcision for religious or cultural indication in the Department of Surgery at KBN Institute of Medical Sciences, Kalaburagi, during February 2016 to January 2018. Children were divided into two groups; neonates (0 to 4 weeks) and infants (5 weeks to1 year). Parents were given specific instructions on care of the device on discharge and followed up on day 3 and on day of separation of the Plastibell. Results: During the study period, 420 cases of Plastibell circumcision fulfilling the inclusion criteria were included and analyzed. Out of the total cases, 120 (28.57%) were neonates, whereas the remaining 300 (71.42%) were infants. Mean surgical time was 4±2 minutes. The mean number of days for Plastibell to separate was 6.2 days, Plastibell ring separation in neonates earlier (3 days to 7 days) as compared to infants (5 days to 12 days). Out of the total 420 cases 65 (15.47%) cases developed minor complications. In neonates, out of 120 cases only 05 (4.16%) developed complications. In infants, out of 300 cases, 60 (20%) developed complications. Conclusions: Neonates had shorter time for the Plastibell to separate and with fewer complications than infants. Though complications were present, they were few and could be managed easily. Plastibell circumcision is safe in neonates and infants.